The effect of exchange rate towards stock markets in Bursa Malaysia / Abidah Suparlan - Suparlan, Abidah (Faculty of Business and Management, 2011)
In this paper investigated the relationship between exchange rate and stock price in Malaysia country. The data are weekly return exchange rate of US dollar in terms of Malaysia Ringgit and weekly return of FTSE Bursa Malaysia KLCI Index, FTSE Bursa Malaysia ACE Index and FTSE Bursa Malaysia EMAS Shariah Index. The period covered to conduct this study is July 2007 to January 2011. This study employs single linear regression Model. Result shows that there was significant relationship between exchange rate and stock indices. There is negative causal relationship from exchange rate to all stock indices.